Assessing phytoplankton community structure in relation to hydrographic parameters and seasonal variation (Pre & Post Monsoon) - M. REZA MIRZAEI; FERESHTEH SERAJI; ELNAZ ERFANIFAR; TEYMOUR AMIN RAD; ZAHRA AMINIKHOEI; BIZHAN AZHANG (Biodiversitas Journal of Biological Diversity, 2017)
Mirzaei MR, Seraji F, Erfani E, Rad TA, Aminikhoei Z, Azhang B. 2017. Assessing phytoplankton community structure in relation to hydrographic parameters and seasonal variation (Pre & Post Monsoon). Biodiversitas 18: 507-513. The present study is conducted to assess hydrographical parameters, phytoplankton composition and the relationship between physicochemical parameters and phytoplankton assemblages along Chabahar coastal waters, South coast of Iran. Based on the collected samples from four stations, all the hydrographical parameters such as sea surface temperature, salinity, pH, DO and nitrate, inorganic phosphate, silicate, and phytoplankton assemblages were studied for five months (from April 2014 to August 2014). A total of 165 phytoplankton groups/taxa were observed in which the Dinophyceae formed the dominant group in all seasons. During the pre-monsoon season, Dinophyceae (56.5%) was the most abundant phytoplankton group followed by Bacillariophyceae (40.8%), Cyanophyceae (1.7 %) and Dictyochophyceae (0.8%). Meanwhile, in the post-monsoon season, Dinophyceae was dominant (49.5%), followed by Bacillariophyceae (46.7%), Cyanophyceae (1.8%), and Dictyochophyceae (1.8%). The highest phytoplankton density was in mid-May (19584953Â± 345182 cell per litter) and the lowest was in late July (163928Â± 1790 cells per liter). Salinity, nitrate, phosphate, silicate showed significant variation (p<0.05) among seasons while pH, seawater temperature, dissolve oxygen did not show significant differences in all stations over the study periods (p<0.05). Phytoplankton density correlated positively with water temperature and salinity. Results showed an increased concentration in phytoplankton density during Pre-monsoon season followed by Post-monsoon and monsoon season.